LINGUISTIC FEATURES OF PHALERONYMIC TERMS IN THE UZBEK LANGUAGE - Safarmurodov Ilxom Turaklovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article examines the linguistic features of phaleronymic terms — names of medals, orders, and other honorary decorations — as they appear in the Uzbek language. Phaleronyms occupy a special place at the intersection of onomastics, lexicology, and sociolinguistics. Focusing on their morpho-phonological shape, lexical-semantic structure, formation strategies, and pragmatic functions in Uzbek, the paper shows how typological properties of Uzbek (agglutinative morphology, productive suffixation, and specific phonotactics) interact with onomastic conventions to produce a characteristic class of lexical items. The study draws on recent onomastic literature and descriptive sources on Uzbek language structure to outline descriptive generalisations and propose directions for further empirical research.